Banks’ external financing costs and the bank lending channel: Results from a SVAR analysis - Breitenlechner, Max; Scharler, Johann; Sindermann, Friedrich (Journal of Financial Stability, 2016)
We analyze the dynamic response of banks’ financing costs to structural, macroeconomic shocks, which we identify by imposing combinations of zero and sign restrictions on impulse responses. For the estimation we combine US bank balance sheet data from the Call reports with macroeconomic aggregates over the period from 1984Q1 to 2007Q3. We find that banks’ financing costs mainly respond to monetary policy and aggregate demand shocks. Furthermore, funding costs of undercapitalized and illiquid banks increase more strongly after a contractionary monetary policy shock as compared to better capitalized and more liquid banks. These results provide support for the view that banks’ financing costs represent an important element of the bank lending channel.